Sexual differences in foraging behaviour in the Lesser Spotted Woodpecker Dendrocopos minor - Hogstad, Olav (Ornis Norvegica, 2010)
Sexual differences in foraging behaviour in the nearly monomorphic Lesser Spotted Woodpecker (Dendrocopos minor) were studied from 1972 to 2007 in a subalpine woodland in central Norway. Data from different years were pooled and analysed on a seasonal basis: winter (November-February), prebreeding (March-April), breeding (May-June) and autumn (September-October). The predominant foraging substrates were in birch Betula odorata (42 % of 460 foraging observations) and grey alder Alnus incana (44 %). No sexual difference was found in use of dead snags, dying broken trees or live trees, for the four periods separately or combined. Both sexes foraged entirely on dead substrates in winter but with the winter period excluded, females foraged more in live trees and less in snags and broken trees than males. The sexes did not differ in use of tree species, except during the winter when females foraged more in birch (73 %) and less in grey alder (22 %) than males (51 % and 49 %, respectively). Females foraged in higher live trees of birch (average height 3.8 m) and grey alder (4.3 m) than males (3.4 m and 3.7 m, respectively) and used substrates with a smaller mean diameter (females: 4.6 cm; males: 5.9 cm). The sexes differed in foraging techniques in each of the periods: males used bark-scaling and pecking more than females in all periods, whereas females used more probing than males during the winter and prebreeding periods and more gleaning (picking in the surface of trunks or branches) outside the winter than males. The sexes overlapped in all foraging dimensions except foraging technique where females tended to have a wider foraging niche in winter and prebreeding periods. Low spatial overlap, division the resources by horizontal separation of the habitat, and a divergence in foraging technique between the sexes all suggest that the Lesser Spotted Woodpecker forage in a way that reduces intersexual competition for food in subalpine woodlands with harsh weather conditions.